Associations between C-reactive protein levels, exercise addiction, and athlete burnout in endurance athletes - Becker, L.; Dupke, A.; Rohleder, N. (Frontiers in Psychology, 2021)
Regular physical activity can support long-term health maintenance, e.g., by reducing inflammatory markers such as C-reactive protein (CRP) levels. However, excessive physical activity can promote the development of both mental and physical illness as well. From a psychological perspective, excessive exercise can lead to the development of exercise addiction (EA) and athlete burnout (AB). However, EA and AB have been rarely investigated so far and it is still unknown whether they are associated with risk factors for physical diseases such as increased CRP levels. In our study, we investigated whether EA and AB in endurance athletes are associated with CRP concentrations. Furthermore, sex differences and prevalence rates of EA were investigated. Ninety-five endurance athletes participated (54.7% female, mean age = 31.8 ± 15.02 years). CRP levels were assessed by means of Dried Blood Spots. For EA and AB assessment, the Exercise Addiction Inventory (EAI) and the Athlete Burnout Questionnaire (ABQ) were used. Exercise addiction was negatively associated with CRP in men. No associations were found for women. None of the ABQ subscales (physical and emotional exhaustion, devaluation of sports, and reduced sense of accomplishment) was associated with CRP levels or with EA. Prevalence of EA was 4.2%. More than 80% of the participants were at risk for EA development. Our results suggest that EA is not necessarily associated with a higher risk for physical diseases through inflammatory pathways. However, EA is a serious mental illness that is widespread in athletes, at least at a subclinical level.